2016
DOI: 10.1016/j.conbuildmat.2016.06.104
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and physicochemical properties of ferro-siliceous concrete subjected to elevated temperatures

Abstract: 1 / 24 Mechanical and physicochemical properties of ferro-siliceous concrete subjected to elevated temperatures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…The mixtures of sacrificial concrete used in the paper were carefully designed according to our previous research findings, as shown in literature [25]. Based on these results, the mixtures of sacrificial concrete for this work were further improved via the addition of GSNSs, and are shown in Table 4.…”
Section: Proportions Of Sacrificial Concretementioning
confidence: 99%
See 2 more Smart Citations
“…The mixtures of sacrificial concrete used in the paper were carefully designed according to our previous research findings, as shown in literature [25]. Based on these results, the mixtures of sacrificial concrete for this work were further improved via the addition of GSNSs, and are shown in Table 4.…”
Section: Proportions Of Sacrificial Concretementioning
confidence: 99%
“…Sacrificial concrete is designed to reduce the leakage potential of radioactive materials in severe nuclear accidents [25]. On one hand, sacrificial concrete can melt and mix with corium (a molten mixture of fuel material, partially or totally oxidized cladding, non-volatile fission products, and various structural materials), reducing the temperature of corium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the relationships between mechanical strengths and UPV of HPCs were different from those of ferro-siliceous concretes, and the compressive strength-UPV and splitting tensile strength-UPV relationships of ferro-siliceous concretes were Weibull distribution and exponential form, respectively [34]. Maybe that was because the deterioration of ferro-siliceous concretes was due to high temperature.…”
Section: Relationships Between Strengths and Upvmentioning
confidence: 98%
“…Although extensive research on the behaviour of concrete subjected to high temperatures has been reported so far [30][31][32][33][34], investigation on the thermal properties of sacrificial concrete is rare, especially on its mechanical properties during elevated temperature exposure. Chu et al [35] have recently carried out a systematic study on mechanical and physicochemical properties of ferro-siliceous sacrificial concrete after high temperature exposure, and observed that the compressive strength-ultrasonic pulse velocity (UPV) and splitting tensile strength-UPV relationships followed a Weibull distribution and was in exponential form, respectively.…”
mentioning
confidence: 99%